Inhibition of Hepatitis C Virus Replication In Vitro by Xanthohumol, A Natural Product Present in Hops - Lou, Sai; Zheng, Yi-Min; Liu, Shan-Lu; Qiu, Jianming; Han, Qunying; Li, Na; Zhu, Qianqian; Zhang, Pingping; Yang, Cuiling; Liu, Zhengwen (Planta Medica, 2014)
Hepatitis C virus is a major cause of chronic liver disease worldwide. Xanthohumol, a prenylated flavonoid from hops, has various biological activities including an antiviral effect. It was previously characterized as a compound that inhibits bovine viral diarrhea virus, a surrogate model of hepatitis C virus. In the present work, xanthohumol was examined for its ability to inhibit hepatitis C virus replication in a cell culture system carrying replicating hepatitis C virus RNA replicon. 0.2 % DMSO and 500 units/mL interferon-alpha treatments were set as a negative and positive control, respectively. The inhibitory effect by xanthohumol was determined by the luciferase activity of the infected Huh7.5 cell lysates and the hepatitis C virus RNA levels in the culture. Xanthohumol at 3.53 µM significantly decreased the luciferase activity compared to the negative control (p < 0.01). Xanthohumol at 7.05 µM further decreased the luciferase activity compared to xanthohumol at 3.53 µM (p = 0.015). Xanthohumol at 7.05 µM or 14.11 µM achieved an inhibitory effect similar to that of interferon-alpha 2b (p > 0.05). Xanthohumol at 3.53 µM significantly reduced the hepatitis C virus RNA level compared to the negative control (p = 0.001). Although the results of xanthohumol at 7.05 µM had a higher variation, xanthohumol at the 7.05 µM and 14.11 µM decreased the hepatitis C virus RNA level to that achieved by interferon-alpha (p > 0.05). In conclusion, xanthohumol displays anti-hepatitis C virus activity in a cell culture system and may be potentially used as an alternative or complementary treatment against the hepatitis C virus.
Keywords: hepatitis C virus; xanthohumol; Humulus lupulus; Cannabaceae; HCV cell culture